Studi Perbandingan Hukum Pidana Islam dan Hukum Positif Terhadap Politik Uang dalam Pemilihan Umum (Pemilu) - Isma, Isma; Idrus, Achmad Musyahid (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2023)
This study analyzes the comparison of Islamic criminal law and positive law on money politics in general elections (elections). This research is expected to provide benefits both scientifically in the study of legal science, as well as practically and academically, that is, it can be used as input for writers, those who have a desire to know how the practice of illegal voting in elections and what the similarities and differences in politics look like. money according to Islamic law and positive law. The research method used in this study is a library research method that is juridical normative, namely research that refers to legal norms that exist in legislation, literature, expert opinions, papers. The laws used in this research are Law No. 10 of 2001 and the Anti-Corruption Law.